2004
DOI: 10.1001/archopht.122.8.1137
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone for the Management of Macular Edema Dueto Nonischemic Central Retinal Vein Occlusion

Abstract: To evaluate the efficacy of intravitreal triamcinolone acetonide in the management of persistent macular edema secondary to nonischemic central retinal vein occlusion (CRVO). Methods: Twenty consecutive patients were selected with a 3-to 4-month history of nonischemic CRVO and persistent macular edema. These patients received a single intravitreal injection of 4 mg of triamcinolone acetonide (40 mg/mL). The follow-up period ranged from 10 to 12 months. The amount of macular edema was assessed by the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Intravitreal triamcinolone treatment has exhibited encouraging results for patients with vascular occlusive diseases and macular oedema. (9)(10)(11)(12)(13)(14)15,16) Similar results were found in our study in eyes with macular oedema secondary to retinal venous occlusion, which showed improvement in mean BCVA from 20/300 at baseline to 20/125 at 15 months (p=0.03). At 15 months, 50% of eyes had improved VA when compared to baseline.…”
Section: Discussionsupporting
confidence: 89%
“…Intravitreal triamcinolone treatment has exhibited encouraging results for patients with vascular occlusive diseases and macular oedema. (9)(10)(11)(12)(13)(14)15,16) Similar results were found in our study in eyes with macular oedema secondary to retinal venous occlusion, which showed improvement in mean BCVA from 20/300 at baseline to 20/125 at 15 months (p=0.03). At 15 months, 50% of eyes had improved VA when compared to baseline.…”
Section: Discussionsupporting
confidence: 89%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal triamcinolone acetonide injection (IVTA) is being increasingly used to treat patients with macular oedema resulting from a variety of conditions such as diabetes, 1,2 retinal vein occlusion, 3,4 pseudophakia, 5 various types of uveitis, 6 radiation retinopathy, 7 and idiopathic cystoid macular oedema (CME). 8 It has also been tried in patients with choroidal neovascular membranes associated with age-related macular degeneration, 9 presumed ocular histoplasmosis syndrome, or choroiditis.…”
Section: Introductionmentioning
confidence: 99%